Examining financial performance of ASEAN REITs from 2020-2022 - Chon, Lorenz Dominick Santos (Animo Repository, 2022)
REITs, or real estate investment trusts, are corporations that own or finance income-generating real estate in various property fields. REITs have generally provided overall competitive returns through high, consistent dividend income and long-term capital appreciation. Asia has started to flourish in recent years and has provided investors with an opportunity to invest in portfolios of real estate with attractive dividend yields. In the case of ASEAN countries, not all have embraced and developed this form of investment due to its unfamiliarity in the region. With this, the paper studies one REIT from each of the five selected ASEAN countries the Philippines, Singapore, Thailand, Vietnam, and Malaysia. This study made use of ASEAN REITs’ stock price, volatility, and dividend yield from 2020-2022. It examined their financial performance to determine which REIT performs the best. The methods used in this study include bootstrapped Value at Risk, Vector Error Correction Model, and Entropy method as weighted criteria to determine the best overall REIT. The study results show that the Philippine REIT (AREIT) and Vietnam REIT (TECHCOM) are the best overall REITs. For the relationship between dividend yield and volatility, there was no sufficient evidence that could correlate their movements.